REPRESENTATIONAL STUDY: MEANING AND SUBJECTIVITY IN PRODUCTION OF SENSE FROM THE OLFACTION SENSE PERCEPTION (Fiep Bulletin - online, 2013)
This study aimed to examine the meaning and subjectivity of the olfaction from the perception of 5th period nursing graduate students from UFRN of 2007.2 semester, registered in the discipline of Mental Health in the Context of Extended Health Clinics. This is an exploratory-descriptive study with quality approach, using a questionnaire containing two open questions. After successive readings, we realize that were focused expressions that helped us to form two categories in which framed the statements of students. Category 1: Nice Smells divided into 4 subcategories, which are: Affection (31.4% cited the smell of "people who love" as more pleasant, and 20% cited the smell of boyfriend / husband), food (51.4 % cited the smell of food and of those, 11.4% specifically cited the "smell of food when you are hungry"); Perfumes (45.7% of citations, specially male perfumes and baby's, with 11.4% of the citations, each), Others (14.3% to nature with an emphasis on roses); Category 2: unpleasant smells (things ruined / garbage, being 51.4%. lack of hygiene with 37.1%, mainly the bromidrosis). The olfaction capacity is aimed at a time when these events and meanings are remindful and, therefore, got a new meaning, generating a representational field to set tastes and aversions on the smell and their memories, whether bringing close those that look pleasant or avoiding the repugnant.
Keywords: Olfaction; Nursing; Mental Health